(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article aims to briefly address the issue of the difficulty of conceptualizing restorative justice, given the various possibilities of its application, considering that it is also necessary that, in each place where it is applied, the restorative practice observes its environment, to define and conceptualize. In a short space, the notion of what would be was exposed, as well as some norms of restorative justice were introduced, at the national level, and, later, in a micro vision, at the Paraná State level. Next, what was intended was to present a brief overview of the advantages and impasses of the application of restorative justice by the Judiciary. It sought to demonstrate how there can be a colonization of restorative practices by the common criminal justice system, at the risk of styling and appeasing the potentials of restorative justice.